Oral Manifestations Related To CD4 Lymphocyte Count in HIV-Positive Patients - Davoodi, Poorandokht (Tabriz University of Medical Sciences, 2010)
BACKGROUND AND AIMS: The onset of opportunistic infections in HIV-positive patients is generally associated with a low CD4 count. Oral manifestations can be the first clinical sign of the infection and also determine the progression of disease. The purpose of this study was to determine the prevalence of oral soft tissue manifestations and their relationship with the degree of immunosuppression observed in HIV-positive patients. MATERIALS AND METHODS: 100 HIV-positive patients were examined. Oral lesions were evaluated according to EEC clearing house criteria. The degree of immunosuppression was based on the CD4 count closest to the oral examination. Data were analyzed using Student’s t-test and chi-square test. RESULTS: The most common oral lesions were rampant caries (54%), periodontal disease (44%), and hyperpigmentation (42%). Salivary glands enlargements and leukoplakia were associated with more severe immunosuppression. CONCLUSION: According to the results, it seems that occurrence of only some of oral lesions are related to the degree of immunosuppression and such lesions can be considered as indicators of the progression of the HIV infection.